Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1016/j.sedgeo.2008.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic susceptibility evolution and sedimentary environments on carbonate platform sediments and atolls, comparison of the Frasnian from Belgium and Alberta, Canada

Abstract: a b s t r a c t a r t i c l e i n f oKeywords: Frasnian Magnetic susceptibility Correlations Platforms and atolls Magnetic susceptibility (MS) measurements on carbonate rocks are considered as a proxy for impurities delivered to the carbonate environments. In the absence of strong climatic or tectonic variations, bulk MS values have been linked to sea level variations, because sea-level fall increases clastic supply and therefore increases in magnetic mineral deposition. In this paper we explore the relationsh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(17 citation statements)
references
References 55 publications
0
16
0
1
Order By: Relevance
“…The magnetic susceptibility (MS) of sediments depends mostly on mineral composition and grain size. In general, iron bearing minerals lead to high values of MS (dimensionless SI units) (e.g., Mullins, 1997;Oldfield, 1991;Da Silva et al, 2009;Reicherter et al, 2010). Terrestrial deposits are often characterized by higher amounts of such minerals compared to marine sediments; therefore MS measurements can help to distinguish between different sedimentary environments.…”
Section: Methodsmentioning
confidence: 99%
“…The magnetic susceptibility (MS) of sediments depends mostly on mineral composition and grain size. In general, iron bearing minerals lead to high values of MS (dimensionless SI units) (e.g., Mullins, 1997;Oldfield, 1991;Da Silva et al, 2009;Reicherter et al, 2010). Terrestrial deposits are often characterized by higher amounts of such minerals compared to marine sediments; therefore MS measurements can help to distinguish between different sedimentary environments.…”
Section: Methodsmentioning
confidence: 99%
“…This time period was selected because, for the Palaeozoic, it has a relatively robust biostratigraphic framework, allowing an essential control to frame the correlations through MS. Furthermore, an important amount of MS data had already been published on the Mid-Palaeozoic Ellwood et al 2001Ellwood et al , 2007Da Silva & Boulvain 2002, 2003, 2006Hladil 2002;Racki et al 2002;Hladil et al 2003Hladil et al , 2006Geršl & Hladil 2004;Whalen & Day 2008;Da Silva et al 2009b). This permitted insertion of the newly collected material (Devonian from the Czech Republic, China, Carnic Alps and Canada; see Da into an already extensive database.…”
Section: Igcp-580 Project: Application Of Ms As a Palaeo-environmentamentioning
confidence: 99%
“…Moreover, MS measurements of Middle Devonian sections of Belgium recently showed that wave agitation is, in combination with terrigenous input, a main inXuencing parameter possibly responsible for non-deposition of MS carrying minerals Boulvain 2007a, b, 2008). The role of carbonate productivity and sedimentation rate has also been considered to lower MS signal by diluting MS carrying minerals (da Silva et al 2008). In order to track these inXuencing parameters within the Ohlesberg quarry, a combination of facies analysis of carbonated-dominated and siliciclastic-dominated facies and their magnetic properties is implemented here.…”
Section: Aims Of the Studymentioning
confidence: 99%
“…The inXuence of carbonate productivity favours lower MS values than expected by diluting the MS carrying minerals (Mabille and Boulvain 2007b;da Silva et al 2008). This is notably obvious for SD2 and SD3.…”
Section: Comparison Between Microfacies and Ms Trendsmentioning
confidence: 99%